Miscellaneous

Misc 1
Deleted for CBSE Board 2023 Exams

Misc 2 Deleted for CBSE Board 2023 Exams

Misc 3 Important Deleted for CBSE Board 2023 Exams

Misc 4 Deleted for CBSE Board 2023 Exams

Misc 5 Deleted for CBSE Board 2023 Exams

Misc 6 Important Deleted for CBSE Board 2023 Exams

Misc 7 Important

Misc 8

Misc 9

Misc 10 Important

Misc 11

Misc 12

Misc 13

Misc 14 Important

Misc 15 Deleted for CBSE Board 2023 Exams You are here

Misc 16 Important Deleted for CBSE Board 2023 Exams

Misc 17

Misc 18

Misc 19 Important

Misc 20

Misc 21 (i) Important Deleted for CBSE Board 2023 Exams

Misc 21 (ii) Deleted for CBSE Board 2023 Exams

Misc 22 Important Deleted for CBSE Board 2023 Exams

Misc 23 Important Deleted for CBSE Board 2023 Exams

Misc 24 Deleted for CBSE Board 2023 Exams

Misc 25 Important Deleted for CBSE Board 2023 Exams

Misc 26 Deleted for CBSE Board 2023 Exams

Misc 27 Deleted for CBSE Board 2023 Exams

Misc 28 Important Deleted for CBSE Board 2023 Exams

Misc 29 Important

Misc 30 Deleted for CBSE Board 2023 Exams

Misc 31 Important

Misc 32 Important Deleted for CBSE Board 2023 Exams

Last updated at May 29, 2018 by Teachoo

Misc 15 The pth, qth and rth terms of an A.P. are a, b, c respectively. Show that (q r) a+(r p)b+ (p q) c = 0 Here we have small a in the equation, so we use capital A for first term We know that, An = A + (n 1) D where An is the nth term of A.P. n is the number of terms A is the first term, D is the common difference It is given that pth term of an AP is a i.e. Ap = a Putting n = p A + (p 1) D = a a = A + (p 1)D qth term of an AP is b i.e. Aq = b Putting n = q A + (q 1)D = b b = A + (q 1)D rth term of an AP is c i.e. Ar = c Putting n = r A + (r 1)D = c c = A + (r 1)D Now we need to show that (q r)a + (r p)b + (p q)c = 0 We have a = A + (p 1)D Multiplying by (q r) a (q r) = [A + (p 1)D] (q r) a (q r) = [A (q r) + (q r) (p 1)D] And b = [A + (q 1)D] Multiplying by (r p) b (r p) = [A + (q 1)D] (r p) b (r p) = [A (r p) + (q r) (q 1)D] Similarly, c = A + (r 1)D multiply this by (p q) c (p q) = [A + (r 1)D] (p q) c (p q) = [A (p q) + (p q) (r 1)D] We have to prove a (q r) + b (r p) + c (p q) = 0 Taking L.H.S a (q r) + b (r p) + c (p q) From (1), (2) & (3) = "[A (q r) + (q r) (p 1)D] + [A (r p) + (r p) (q 1)D]" "+ [A (p q) + (p q) (r 1)D]" = "A (q r) + A (r p) + A (p q) + (q r) (p 1)D" "+ (r p) (q 1)D + (p q) (r 1)D" = A[q r + r p + p q] + D[(q r) (p 1) + (r p) (q 1) + (p q) (r 1)] = A[p p + r r + q q] + D[q(p 1) r(p 1) + r(q 1) p(q 1) + p(r 1) q(r 1)] = A[0 + 0 + 0] + D[qp q rp + r + rq r pq + p + pr p qr + q] = 0 + D[qp pq + rq qr rp + pr + q q + r r + p p ] = 0 + D[0] = 0 = R.H.S Hence proved